Feasibility Study of A New Concept “Warung Mie” Store of XYZ Restaurant in Amsterdam - Felicia Hana; Kurnia Fajar Afgani (Mandalika Institute, 2024)
XYZ restaurant is a takeaway restaurant offering homemade Indonesian dishes located in Amsterdam. After 3 years of operating, restaurant XYZ realized that the majority of customers pick noodles as their most favorite dish, which tends to sell out every day. The restaurant identified an opportunity to focus on noodle-based dishes by establishing a Warung Mie concept store in Amsterdam. This decision is supported by Amsterdam's status as an international city with a diverse culinary scene and the potential growth of the noodle market in the Netherlands. Moreover, many Dutch people are familiar with Indonesian cuisine. The project requires an initial investment of €154,062. Therefore, before implementing the project, the owner would like to analyze its feasibility and associated risks, which is the purpose of this study. There are five stages in constructing the feasibility study: constructing pro forma financial statements, calculating the weighted average cost of capital, calculating free cash flow to the firm (FCFF), conducting a financial feasibility analysis, and performing a risk assessment. The tools used to assess feasibility include the payback period (PP), net present value (NPV), internal rate of return (IRR), and profitability index (PI). Moreover, sensitivity analysis is used to conduct the risk analysis and assess the project's resilience to changes in key variables. Based on the market and financial analysis, the project is feasible and will generate profit in the future. The payback period would be 5 years, 1 month, and 3 days; NPV is €210,176; IRR is 19.5%; and PI is 2.4. The sensitivity analysis highlights that variations in total sales are the most impactful variable to the NPV, followed by salaries and wages. Therefore, restaurant XYZ is advised to focus on improving total sales. Additionally, implementing effective financial monitoring and control systems will help manage sales and salary expenses efficiently, mitigating potential risks associated with fluctuations in these variables.